2018
DOI: 10.3233/jvr-180929
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to employment as reported by people with physical disabilities: An across disability type analysis

Abstract: BACKGROUND: Extant research has reported on the factors associated with seeking and maintaining employment for individuals with different types of physical disabilities, such as cerebral palsy (CP), multiple sclerosis (MS), and spinal cord injuries (SCI). Some of these factors are barriers and others are facilitators. However, research has not determined whether the inhibiting and facilitating employment experiences of people with physical disabilities are similar across type of physical disability. OBJECTIVE:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Within the workplace, even when accessibility was made possible through devices, malfunctioning of technologies such as lifts impacted on job accessibility [43]. Transportation to work was often problematic, particularly for people with a spinal cord injury [20,42], multiple sclerosis, cerebral palsy [20], and traumatic brain injury [44] due to restrictions on ability to drive. To be a viable opportunity, a potential job needed to be geographically accessible and able to be reached within a reasonable amount of time [20].…”
Section: Accessibility Of the Workplace And The Work Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the workplace, even when accessibility was made possible through devices, malfunctioning of technologies such as lifts impacted on job accessibility [43]. Transportation to work was often problematic, particularly for people with a spinal cord injury [20,42], multiple sclerosis, cerebral palsy [20], and traumatic brain injury [44] due to restrictions on ability to drive. To be a viable opportunity, a potential job needed to be geographically accessible and able to be reached within a reasonable amount of time [20].…”
Section: Accessibility Of the Workplace And The Work Environmentmentioning
confidence: 99%
“…Transportation to work was often problematic, particularly for people with a spinal cord injury [20,42], multiple sclerosis, cerebral palsy [20], and traumatic brain injury [44] due to restrictions on ability to drive. To be a viable opportunity, a potential job needed to be geographically accessible and able to be reached within a reasonable amount of time [20]. The necessity of using public transport or relying on friends and family introduced concerns regarding timeliness and reliability, particularly for those who resided in rural areas [20,42,43].…”
Section: Accessibility Of the Workplace And The Work Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Most individuals with IDD do not drive, and so they require transportation to work (Bezyak, Sabella, & Gattis, 2017). Across disability types, access to transportation, physical location, and travel requirements were noted as major considerations in finding and keeping employment (Graham, Inge, Wehman, Seward, & Bogenschutz, 2018). McCausland, Stancliffe, McCallion, and McCarron (2019) reported that older people with IDD in Ireland mostly used transportation provided by disability staff to attend work or day programs, with a minority traveling independently using public transportation.…”
mentioning
confidence: 99%